Clinical complaints and their handling: a time for change?. Issue 1 (March 1992) - Donaldson, L J; Cavanagh, J
Abstract : OBJECTIVES--To assess the performance of the hospital complaints procedure for complaints proceeding to peer review and the quality of responses to complainants. DESIGN--Retrospective study of data on clinical complaints proceeding to peer review during 1986-91 from clinical records, correspondence, reports of the complaints investigations, and expert review of written responses to complainants. SETTING--Northern Regional Health Authority, covering three million people. SUBJECTS--All 71 clinical complaints investigated to the third stage of the hospital complaints procedure and a sample of 65 written responses to complainants. MAIN MEASURES--Characteristics, duration, and outcome of complaints; findings of peer review; and quality of written responses at various stages in the procedure as evaluated by an expert panel against eight agreed criteria. RESULTS--The median duration of a complaint investigated through all stages of the procedure was 381 days. The longest median stages were those involving attempted resolution locally (131 days) and in which peer review was being arranged (113 days). More complaints alleging failure of communication were upheld by peer review (46/59, 78%) than those alleging misapplication of clinical skills (20/98, 20%) or failure to initiate appropriate investigations or treatment (8/32, 25%). Written responses commonly fell below the standards agreed by the expert panel. CONCLUSIONS--The hospital complaints procedure takes too long and its final peer review stage may not demonstrate sufficient impartiality. The written responses suggest that criticism is not welcomed as a way of improving service. IMPLICATION--The clinical complaints procedure needs to be reformed to ensure true accountability to patients.